Ubisch bodies and pollen ontogeny in Oxalis articulata Savigny - Rosenfeldt, S. (2005)
The correlation between the ontogeny of Ubisch bodies and pollen development in Oxalis articulata was studied with Transmission Electron Microscopy (TEM). The ultrastructural changes observed during the different stages of development in the tapetal cells are related to Ubisch bodies, sporopollenin and pollen-kitt formation. The pro-orbicules have the appearance of lipid globuli and their formation is related to the endoplasmic reticulum of rough type (ERr). The lipid globules or pro-orbicules disappear in the mature Ubisch bodies, and the places that they occupied remain free of contents or with pollen-kitt.